High bleeding risk in all-comers with ST-segment elevation myocardial infarction and use of P2Y12-inhibitiors. (3rd October 2022) - Jacobsen, M R; Jabbari, R; Engstroem, T; Grove, E L; Glinge, C; Pedersen, F; Holmvang, L; Koeber, L; Torp-Pedersen, C; Maeng, M; Veien, K; Freeman, P; et al.
Abstract: Background: Bleeding has an important prognostic impact in patients with ST-segment elevation myocardial infarction (STEMI), yet stratification of bleeding risk to guide dual antiplatelet therapy (DAPT) is not routinely performed in clinical practice. Purpose: To describe high bleeding risk (HBR) patients according to the PRECISE-DAPT (predicting bleeding complications in patients undergoing stent implantation and subsequent DAPT) score and use of P2Y12-inhibitors. Methods: This single-centre observational study included consecutive patients with STEMI who were treated with percutaneous coronary intervention (PCI) from 2009–2016. Individual linkage to Danish nationwide registries was conducted to obtain information on diagnoses, claimed drugs, and vital status. Age, prior bleeding diagnosis, and blood samples before PCI (maximum 30 days before hospitalisation) were used to calculate the PRECISE-DAPT score. A score ≥25 was considered as HBR. Due to 26.7% missing on blood parameters (mainly leucocytes), the maximum and minimum values of the missing parameters and respective imputed PRECISE-DAPT scores were calculated. If both the maximum and minimum score were ≥25 or <25, patients were categorised accordingly, and a maximum score of ≥25 and minimum score of <25 as missing. Differences between continuous (median [interquartile range, IQR]) and categorical variables (frequency [percentage]) were assessed using Wilcoxon rank-sum and χ 2 -test for patients with vs. without HBR. Cumulative incidence of major bleeding (composite of bleedings leading to hospitalisation) and major adverse cardiovascular events (MACE) (composite of all-cause mortality, recurrent MI, and ischemic stroke) 1 year after PCI were plotted for patients with and without HBR. Number of HBR patients alive and collecting a P2Y12-inhibitor prescription within 30 days from discharge was reported. Results: We identified 6179 PCI-treated patients with STEMI, of whom 5530 (89.5%) had imputed PRECISE-DAPT scores (Figure 1). A total of 1821 (32.9%) were at HBR, and these were more often female (38.3 vs. 18.2%, p-value<0.001), elderly (median age 75 [IQR 67, 81] vs. 57 years [IQR 51, 64], p-value<0.001), and had more comorbidities (diabetes [16.7 vs. 12.1%], heart failure [16.2 vs. 7.6%], cardiac arrhythmia [24.9 vs. 12.3%], cancer [17.5 vs. 5.7%], and ischemic stroke [8.1 vs. 2.6%], all p-values<0.001) compared with patients not at HBR. One-year cumulative incidence of major bleeding and MACE for patients with and without HBR were plotted (Figure 2). Of the 1431 (78.6%) HBR patients who were alive and claimed a P2Y12-inhibitior prescription 30 days from discharge, 459 (32.1%) were treated with clopidogrel, 672 (46.9%) with ticagrelor, and 300 (21.0%) with prasugrel (Figure 1). Conclusion: Every third PCI-treated all-comer with STEMI was at HBR according to the PRECISE-DAPT score. HBR patients were more often treated with potent P2Y12-inhibitors (prasugrel or ticagrelor) instead of clopidogrel. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship.